Influence of circulating nesfatin-1, GSH and SOD on insulin secretion in the development of T2DM - Huang, Kangkang; Liang, Yunlai; Wang, Kun; Wu, Jiahui; Luo, Huidan; Yi, Bin (Frontiers in Public Health, 2022)
Aims: To evaluate the correlation of nesfatin-1, GSH and SOD levels with β-cell insulin secretion and their influence on insulin secretion in the development of type 2 diabetes mellitus (T2DM). Materials and methods: 75 patients with T2DM, 67 with prediabetes and 37 heathy participants were recruited in this study. Serum levels of nesfatin-1, GSH and SOD were quantified and statistically analyzed. Results: The levels of nesfatin-1, GSH and SOD in T2DM were significantly decreased (P<0.001) compared to either in prediabetes or in healthy control, and significant reduction of these biomarkers was also observed in prediabetes when compared to the control (P<0.001). Circulating nesfatin-1, GSH and SOD were not only strongly correlated with β-cell insulin secretion, but also exerted remarkable influence on the secretion. Conclusion: Serum nesfatin-1, GSH and SOD are important factors involving insulin secretion in the development of T2DM, which may help provide new ideas for forthcoming investigations on the roles of these factors in pathogenesis of T2DM, as well as for active prediction and prevention of prediabetes before it develops into overt T2DM.